Pengaruh Green Accounting, Kinerja Lingkungan, Biaya Lingkungan, Pengungkapan Corporate Social Responsibility Dan Ukuran Perusahaan Terhadap Profitabilitas - Lusiana, Prima Aprilia; Mujiyati (Institut Agama Islam Negeri (IAIN) Madura, 2025)
Environmental issues that have been in the spotlight recently, such as pollution, climate change, and natural resource degradation, are the driving factors for this study. The company's production activities have a major impact on the environment, especially manufacturing companies in the non-cyclical consumer sector. Therefore, companies must strategize sustainable and environmentally friendly business methods. This study examines the effect of green accounting, environmental performance, environmental costs, corporate social responsibility disclosure, and company size on profitability in manufacturing companies in the non-cyclical consumer sector listed on the Indonesia stock exchange from 2021-2023. Purposive sampling is the sampling strategy used in this study, and secondary data such as sustainability reports and annual reports are used for data collection. 15 companies have met the requirements to become observation units. The data analysis technique used is multiple linear regression analysis and classical assumption test using SPSS 25 as a test tool. These findings provide factual evidence that company size significantly affects its profitability. Meanwhile, manufacturing companies in the non-cyclical consumer goods sector listed on the Indonesia Stock Exchange for 2021-2023 did not experience changes in profitability as a result of green accounting, environmental performance, or corporate social responsibility disclosure.